The Role of Network Capabiliity in Shaping Behavior E-commerce Acceptance Among Small Businesses in Keranggan Village - Yuniarty Yuniarty; Hartiwi Prabowo; Ridho Bramulya Ikhsan (Bina Nusantara University, 2020)
This research is a case study to help identify the driving factors of e-commerce acceptance by small businesses in Keranggan Village in Indonesia. This study argues that factors such as technology-organization-environment need to be strengthened by network capability from business actors so that e-commerce adoption intention emerges. From the total samples of 100 business actors in Keranggan Village. The study utilized Structural Equation Modeling (SEM) with SmartPLS 3.0 for data examination. Consequently, the relationship of technological context with e-commerce acceptance is mediated by significant network capability.